لباس المرأة بين حقوق الإنسان والشريعة الإسلامية - حسن، موسى أنور (al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2013)
This study addresses the issue of Muslim women's attire based on the Islamic Shariah Law and its relation to the human rights declared by the United Nations. This thesis has three chapters; the first chapter presents the preliminary introduction to the research including the rationale for the topic, the research problem, literature review and the research methodology. The second chapter discusses the concept of attire in the Islamic Shariah Law and in the Muslim customs and the conditions required for dressing according to Islamic Shariah Law. The third chapter describes the issue of human rights historically and its relation to Islamic women's attire in light of the issue of women's liberalization in accordance with human rights and campaigns against the Islamic dress code in the name of those rights. The researcher adopted two methods in this study; the inductive method in tracking and collecting the scientific material and the analytical methods to find out how Islam has elevated the status of women, gave them rights that they had never enjoyed before, and imposed some duties on them in order for them to fill and perform their role in building the community. The research deeply focuses on analyzing the issue of Islamic attire and illustrates points of view of both the Islamic and the human rights' advocates on the issue. This analysis concludes by stressing on the nobility of the Islamic perspective and its goal behind the Islamic veil or dress code. On the other hand, the analysis exposes the malicious intentions of the West, which aim at the destruction of the Muslim community, by demolishing the most important pillar of the Muslim society, the Muslim women. This research concludes with several results such as the legitimacy of the Islamic attire being proven by unequivocal evidences, that the issue of exposure or cover of face and palms is a controversial issue and the rejection and ban of the Islamic veil in some Western countries show their contradictory attitudes toward personal religious freedom.